2009
DOI: 10.3346/jkms.2009.24.4.636
|View full text |Cite
|
Sign up to set email alerts
|

The Area of Ground Glass Opacities of the Lungs as a Predictive Factor in Acute Paraquat Intoxication

Abstract: Even though plasma paraquat (PQ) levels have known to be an informative predictor, many patients succumb at low PQ levels in acute PQ intoxication. This study was designed to see whether the high resolution computerized tomography (HRCT) of the lungs would be a predictive measure in acute PQ intoxication. HRCT of the lungs was obtained from 119 patients with acute PQ intoxication on 7 days after PQ ingestion. The areas with ground glass opacities (GGOs) were evaluated at five levels with the area measurement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The volume of ingested PQ was determined on the basis of adult mouthful swallow, with a mean volume of approximately 20 mL, which is in agreement with previous reports [25][26][27]. However, in some instances, the precise amount of PQ ingested could not be confirmed especially for subjects who got exposed to PQ by drinking from a bowl, cup or glass.…”
Section: Discussionsupporting
confidence: 86%
“…The volume of ingested PQ was determined on the basis of adult mouthful swallow, with a mean volume of approximately 20 mL, which is in agreement with previous reports [25][26][27]. However, in some instances, the precise amount of PQ ingested could not be confirmed especially for subjects who got exposed to PQ by drinking from a bowl, cup or glass.…”
Section: Discussionsupporting
confidence: 86%
“…Because the extent of lung injury is very important for predicting patient mortality in clinical situations [28,29], it is noteworthy that CP attenuated the extent of PQ-induced lung lesions as determined by micro-CT images in our study. This finding has not been reported previously.…”
Section: Discussionmentioning
confidence: 65%
“…Serum levels of PQ have been widely used to assess the accumulation of dangerous lung uptake, which normally peaks 4-5 h following exposure, although some studies reported that maximum lung concentration occurs as late as 15 h after exposure [7]. Plasma PQ levels have long been considered the most valuable prognostic indicator, but they have been shown to be highly variable between individuals, necessitating further examination by CT scanning and other imaging methods [12,13]. Because the serum response time varies, investigation by tissue biopsy may yield more accurate results [14].…”
Section: Discussionmentioning
confidence: 99%